Service Quality Analysis of JakLingko Mobile Application in Jakarta’s Public Transportation - Ayuningtias, Anadya; Pramono, Sidik (Indonesian Association for Public Administration (IAPA), 2025)
In today’s digital era, technology has been adapted into various aspects of society, including public transportation. One such application available to the public is the JakLingko app. This application develops a Mobility as a Service (MaaS) model, which is a single application for various modes of transportation. The available transportation modes include TransJakarta, Jakarta MRT, Jakarta LRT, and KRL Commuter Line. The JakLingko application, with its integration concept, is expected to facilitate public access to public transportation through the features available on the application. However, in reality, there are members of the public who frequently encounter difficulties when using the application. Therefore, this study aims to analyze the quality of electronic services on the JakLingko app. The approach used is quantitative, with data collection techniques including an online survey of 135 respondents. The study also employs a qualitative method through interviews and literature reviews, which serve as supporting data. The results indicate that the quality of electronic services on the JakLingko app is of high quality. This finding is supported by several dimensions and measurement indicators, which also received high ratings from JakLingko app users.